ANALISIS ERGONOMI DESAIN KURSI KERJA KARYAWAN DI PT. YYY - Deasy M Pardede; A. Rahim Matondang; Listiani Nurul Huda (Departemen Teknik Industri Universitas Sumatera Utara, 2013)
PT. YYY is a company engaged in the production of antimosquito. The problems faced by the company is not ergonomic chair sorters. It’s height is not compatible with the work area (oven baking sheet) and doesn’t have a backrest. It resulted a risk in a working posture sorter. If allowed to continue, may lead to musculoskeletal disorders (MSDs). The research used qualitative and quantitative methods. Qualitative method with SNQ (standar Nordic quetionaire) and comfortable quetionaire. SNQ is used to know the pain in part of body as a resulted not ergonomic chair sorters. Quantitative method with measure body dimension of sorters and redesign chair’s sorter by antropometric approach. In antropometric approach, do some testing. That is : uniformity test, adequacy test, normality test, and percentile value determination. Shoulder breadth and sitting shoulder height was proceed by 95 percentil, while buttock-popliteal was proceed by 50 percentile.The samples used were as many 39 sorter employees. SNQ shows that employees have pain in someparts of their body such as hips and buttocks. The result showed that risk reduction of MSDs. Actual working posture get level 6 which indicate that chair improvement is important, while employees’working postures with redesigned chair get level 3. Level 3 showed risk reduction on employees